Lanthanide (Ce, Nd, Eu) environments and leaching behavior in borosilicate glasses - M. Fabian (Nature Portfolio, 2021)
Abstract Borosilicate glasses will be used to stabilize the high-level radioactive wastes for disposal in a geological repository. Understanding the effects of actinide addition to a borosilicate glass matrix is of great importance in view of waste immobilization. Lanthanides were considered as chemical surrogates for actinides. The local structures of Ce3+, Nd3+ and Eu3+ ions in borosilicate glass, have been investigated by synchrotron radiation based techniques. The atomic parameters, such as bond lengths and coordination environments derived from X-ray diffraction, in combined with Reverse Monte Carlo simulations show correlation with X-ray absorption fine structure data. The lanthanide ions are in the common network with the tetrahedral SiO4 and with the mixed trigonal BO3 and tetrahedral BO4 units. Second neighbor atomic pair correlations reveal that the Ce3+, Nd3+ and Eu3+ ions are accommodated in both Si and B sites, supporting that the lanthanide-ions are stabilized in the glass-matrix network. Microscopy and microanalysis provided information on the amorphous state and on the major elemental composition of the high lanthanide-concentration samples. The release of matrix components (Si, B, Na, Ba, Zr) is higher than that of lanthanides (Ce, Nd, Eu). Both types of elements show a decreasing release tendency with time.